(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the role of sport not only as a means of physical health improvement but also as a powerful tool for social integration within "mahalla" (local community) settings. The study highlights the socio-psychological significance of broadly involving various population strata, specifically the elderly, youth, and persons with disabilities, in mass sports. The author examines existing barriers in this field and proposes innovative approaches regarding the adaptation of sports infrastructure based on inclusive requirements, the use of digital technologies, and the implementation of motivational systems at the community level. Consequently, new mechanisms are developed for the mahalla institution to strengthen public health and enhance social cohesion in society.